Análise do nível de relação entre disfunção temporomandibular e estresse psicológico em atletas de futebol - Cornelis Robert Araújo Springer (2020)
ABSTRACT Performance sports can result in acute and chronic psychological stress. Athletes who report higher levels of psychological stress, recover from fatigue and pain more slowly, experiencing a different perceived energy recovery. There is evidence that stress leads to increased muscle and temporomandibular joint activity, causing Temporomandibular Dysfunction (TMD). The impact of pain caused by TMD on work activities has been of great relevance in recent studies. It is intended, then, as the objective of this study, to verify the level of relationship between TMD and psychological stress in soccer athletes. To analyze the level of relationship between TMD and psychological stress in soccer athletes, an observational, exploratory, cross-sectional study was conducted in a Brazilian soccer club, with 94 athletes, being 18 athletes from the female professional team and 76 athletes from the male grassroots categories. To evaluate the athletes' TMD, the questionnaire called Fonseca's Anamnetic Index (1994) of ten questions was used and to evaluate the psychological stress of the athletes, the perceived stress scale of fourteen questions (PSS-14) was used, translated and adapted for the Portuguese language by Luft (2006). Data were analyzed using SPSS version 25.0 for IOS, adopting a 5% significance level and the power of the results was calculated using the Gpower® 3.1.9.2 software. The results showed that of the sample of 94 athletes studied, 53 athletes (56.38%) had TMD and 70 athletes (74.47%) had psychological stress. Most athletes are in high school (75 athletes - 79.7%), with a monthly family income considered good by 71 athletes (75.5%). 75 athletes (79.7%) competed in four to six championships per season and 72 athletes (76.6%), responded with good sleep quality. The correlation between TMD and psychological stress was confirmed by the Pearson correlation test, being moderate and positive for athletes from the under-15 and under-17 teams (r = 0.78 and r = 0.56 respectively). The correlation was strong and positive for the under-20 and female professional teams (r = 0.89 for both teams). The correlation results showed a significance of p≤0.05 for the under-17 team and p≤0.01 for the other teams. The results of the simple linear regression pointed to dependence between the variables, also with a significance of p≤0.05 for the under-17 team and p≤0.01 for the other teams. The straight equations, results of simple linear regression for each team, can predict TMD scores from perceived stress scores for these soccer athletes. The calculated power was 0.88 for the under-17 team and 1.00 for the other teams. It is concluded that TMD is positively influenced by psychological stress in soccer athletes from the teams described above and that the results of TMD prediction can collaborate in the selection of athletes for later clinical care.